2014
DOI: 10.1097/mog.0000000000000117
|View full text |Cite
|
Sign up to set email alerts
|

Role of programmed necrosis and cell death in intestinal inflammation

Abstract: The role of cell death in the intestine is complex and its potential implication in intestinal diseases, and inflammatory bowel disease in particular, needs to be reevaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 73 publications
0
17
0
1
Order By: Relevance
“…Here our purposes are thus simply to recognise that the genes induced or repressed via transcription factors such as NF-kB can be pro-or antiapoptotic, and which ones are activated depend on all prevailing conditions. As well as apoptosis, there is a less tightly (but partly) regulated form of cell death known as 'programmed necrosis' or 'necroptosis', [425][426][427][428][429][430][431][432][433][434][435][436][437] that may be induced by inflammatory ligands such as TNF, especially during infection, and that sometimes also involve NF-kB. Another important mode of cell death induced by related stimuli is pyroptosis [438][439][440][441][442][443][444][445][446][447][448][449][450] (that involves the caspase 1-dependent production of IL-1b).…”
Section: Lps Induction Of Apoptotic Programmed Necrotic and Pyroptotmentioning
confidence: 99%
“…Here our purposes are thus simply to recognise that the genes induced or repressed via transcription factors such as NF-kB can be pro-or antiapoptotic, and which ones are activated depend on all prevailing conditions. As well as apoptosis, there is a less tightly (but partly) regulated form of cell death known as 'programmed necrosis' or 'necroptosis', [425][426][427][428][429][430][431][432][433][434][435][436][437] that may be induced by inflammatory ligands such as TNF, especially during infection, and that sometimes also involve NF-kB. Another important mode of cell death induced by related stimuli is pyroptosis [438][439][440][441][442][443][444][445][446][447][448][449][450] (that involves the caspase 1-dependent production of IL-1b).…”
Section: Lps Induction Of Apoptotic Programmed Necrotic and Pyroptotmentioning
confidence: 99%
“…Since the discovery and naming of necroptosis in 2005, it has been demonstrated that necroptosis may participate in the pathology of a number of inflammation diseases, such as acute pancreatitis (Wang, Qu, Li, Lv, & Sun, ), ischemia–reperfusion injury (Zhang et al., ), inflammatory bowel disease (IBD) (Dagenais, Douglas, & Saleh, ), and skin diseases (Panayotova‐Dimitrova et al., ). In addition, human cytomegalovirus (Omoto et al., ), as well as herpes simplex virus I and II (Guo et al., ), inhibited necroptosis to facilitate the intracellular proliferation and growth, whereas interaction of HSV‐1 protein ICP6 with RIPK1 and RIPK3 triggers necroptosis, thus limiting viral propagation in experimental animals (Huang et al., ), which demonstrated a different role of necroptosis in virus infection‐related diseases.…”
Section: Necroptosis In the Homeostasis Of Periodontal Tissuementioning
confidence: 99%
“…Accumulating evidence implicates both apoptosis and a novel form of regulated necrosis termed necroptosis in intestinal chronic inflammation and pathology. 5 A key inducer of both cell death forms is the proinflammatory cytokine tumor necrosis factor-a (TNFa) that exerts important pathological effects in IBD. Indeed, anti-TNFa monoclonal antibody therapy is currently the main biological treatment for IBD patients.…”
Section: Introductionmentioning
confidence: 99%